“Shared Press Distress” and the Police Raid on a Newspaper - Mathews, Nick; Wolgast, Stephen (The Journal of communication inquiry, 2026)
This article introduces the concept of shared press distress—the emotional and psychological strain of watching, reading, or hearing about a fellow journalist's trauma or distress. Shared press distress does not stem from direct exposure to trauma but rather from the far-reaching ripple effect one journalist's distress can have on others in the profession. This concept is grounded in the lived experience of 19 journalists in Kansas, where police raided a fellow state newspaper. The in-depth interviews revealed emotional and practical responses from the journalists. Emotionally, there was a sense of disbelief as they watched a colleague endure a perceived violation of press freedoms. On the practical side, witnessing a fellow journalist face a perceived retaliatory raid for carrying out the core function of accountability journalism compelled them to reassess themselves, raising difficult questions about the risks of holding the powerful in check. The emotional weight of the experience and the practical reevaluation intertwined, emphasizing the grim reality that if it could happen to one Kansas journalist, it could happen to any of them—an attack not just on one newsroom, but on journalism itself.